Mesomelia-synostoses syndrome: contiguous deletion syndrome, SULF1 haploinsufficiency or enhancer adoption? - Ingrid Bendas Feres Lima; Lúcia de Fátima Marques de Moraes; Carlos Roberto da Fonseca; Juan Clinton Llerena Junior; Mana Mehrjouy; Niels Tommerup; Elenice Ferreira Bastos (Molecular Cytogenetics, 2024)
Abstract Background Mesomelia-Synostoses Syndrome (MSS)(OMIM 600,383) is a rare autosomal dominant disorder characterized by mesomelic limb shortening, acral synostoses and multiple congenital malformations which is described as a contiguous deletion syndrome involving the two genes SULF1 and SLCO5A1. The study of apparently balanced chromosomal rearrangements (BCRs) is a cytogenetic strategy used to identify candidate genes associated with Mendelian diseases or abnormal phenotypes. With the improved development of genomic technologies, new methods refine this search, allowing better delineation of breakpoints as well as more accurate genotype-phenotype correlation. Case presentation We present a boy with a global development deficit, delayed speech development and an ASD (Asperger) family history, with an apparently balanced “de novo” reciprocal translocation [t(1;8)(p32.2;q13)dn]. The cytogenetic molecular study identified a likely pathogenic deletion of 21 kb in the 15q12 region, while mate pair sequencing identified gene-truncations at both the 1p32.2 and 8q13 translocation breakpoints. Conclusions The identification of a pathogenic alteration on 15q12 involving GABRA5 was likely the main cause of the ASD-phenotype. Importantly, the chr8 translocation breakpoint truncating SLCO5A1 exclude SLCO5A1 as a candidate for MSS, leaving SULF1 as the primary candidate. However, the deletions observed in MSS remove a topological associated domain (TAD) boundary separating SULF1 and SLCO5A1. Hence, Mesomelia-Synostoses syndrome is either caused by haploinsufficiency of SULF1 or ectopic enhancer effects where skeletal/chrondrogenic SULF1 enhancers drive excopic expression of developmental genes in adjacent TADs including PRDM14, NCOA2 and/or EYA1.